2013
DOI: 10.1039/c3mt00060e
|View full text |Cite
|
Sign up to set email alerts
|

Iron distribution through the developmental stages of Medicago truncatula nodules

Abstract: Paramount to symbiotic nitrogen fixation (SNF) is the synthesis of a number of metalloenzymes that use iron as a critical component of their catalytical core. Since this process is carried out by endosymbiotic rhizobia living in legume root nodules, the mechanisms involved in iron delivery to the rhizobia-containing cells are critical for SNF. In order to gain insight into iron transport to the nodule, we have used synchrotron-based X-ray fluorescence to determine the spatio-temporal distribution of this metal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
77
0
11

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(92 citation statements)
references
References 50 publications
4
77
0
11
Order By: Relevance
“…Because iron is released into the apoplast of zone II cells, and because little or no iron remains in the zone III apoplast (Rodríguez-Haas et al, 2013), the conclusion is that Nramp or ZIP transporter(s) must mediate iron uptake from the apoplast into the cytosol of cells in this region of the nodule. Promoter::gus fusion data and the gene expression information from the Symbimics database for MtNramp1 indicated that the gene is expressed in zone II of the nodule.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because iron is released into the apoplast of zone II cells, and because little or no iron remains in the zone III apoplast (Rodríguez-Haas et al, 2013), the conclusion is that Nramp or ZIP transporter(s) must mediate iron uptake from the apoplast into the cytosol of cells in this region of the nodule. Promoter::gus fusion data and the gene expression information from the Symbimics database for MtNramp1 indicated that the gene is expressed in zone II of the nodule.…”
Section: Discussionmentioning
confidence: 99%
“…Synchrotron-based x-ray fluorescence results indicate that, at least in indeterminate nodules, iron is primarily delivered by the vasculature and released into the apoplast of zone II (Rodríguez-Haas et al, 2013). In this zone and probably in the interzone with the nitrogen-fixing zone III, iron has to be delivered from apoplast into cells before it is transported to the bacteria in symbiosomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intact nodules were imaged using a stereoscopic microscope Nikon SMZ-U (Nikon) and SPOT 5.1 software (Diagnostic Instrument). Nodules were fixed in buffer containing 4 % paraformaldehyde, 0.25 % glutaraldehyde and 2.5 % sucrose in 50 mM potassium phosphate buffer, pH 7.4, and incubated overnight at 4 uC with gentle agitation (Rodríguez-Haas et al, 2013). Dehydration was carried out using a graded ethanol series (0, 30, 50, 70, 85, 90, 95, 100 %) at 4 uC.…”
mentioning
confidence: 99%
“…De hecho, la deficiencia de cobre en suelos reduce la actividad fijadora de nitrógeno de los nódulos (Hallsworth, 1960;Seliga, 1993;Snowbal et al, 1980). Al igual que ocurre con el hierro, se hipotetiza que el cobre viaja por los haces vasculares desde la raíz al nódulo y se libera en el apoplasto de la zona de infección/ diferenciación de los nódulos de tipo indeterminado (Rodríguez-Haas et al, 2013).…”
Section: Mtcopt1unclassified